Depth variations in seismic velocity in the subducting crust: Evidence for fluid‐related embrittlement for intermediate‐depth earthquakes. Issue 2 (28th January 2017) - Shiina, Takahiro; Nakajima, Junichi; Matsuzawa, Toru; Toyokuni, Genti; Kita, Saeko
Abstract: We investigated seismic wave velocity in the subducting crust of the Pacific slab beneath eastern Hokkaido, northern Japan. To detect depth‐dependent properties of the seismic velocities in the crust, we analyzed guided waves that propagate in the crust and estimated P wave velocity ( Vp ) of 6.5–7.5 km/s and S wave velocity ( V s ) of 3.6–4.2 km/s at depths of 50–100 km. The results show that the obtained Vp and Vs are 10–15% lower than those expected for the fully hydrated mid‐ocean ridge basalt, suggesting the existence of aqueous fluids by 1 vol % in the crust at this depth range. Our observations suggest that overpressurized fluids channeled in the subducting crust plays as a dominant factor for facilitating the genesis of crustal earthquakes at intermediate depths. Key Points: We estimate seismic velocity in the subducting crust beneath eastern Hokkaido by using guided waves Observed Vp and Vs are lower than those expected for the hydrated MORB at depths of 50–100 km The amount of fluids channeled in the crust would contribute to the facilitation of crustal seismicity